The Trajectory Towards a Seasonally Ice-Free Arctic Ocean - Notz, Dirk (Curr Clim Change Rep, 2018)
PURPOSE OF REVIEW: The observed substantial loss of Arctic sea ice has raised prospects of a seasonally ice-free Arctic Ocean within the foreseeable future. In this review, we summarize our current understanding of the most likely trajectory of the Arctic sea-ice cover towards this state. RECENT FINDINGS: The future trajectory of the Arctic sea-ice cover can be described through a deterministic component arising primarily from future greenhouse gas emissions, and a chaotic component arising from internal variability. The deterministic component is expected to cause a largely ice-free Arctic Ocean during summer for less than 2 (∘)C global warming relative to pre-industrial levels. To keep chances below 5 % that the Arctic Ocean will largely be ice free in a given year, total future CO(2) emissions must remain below 500 Gt. SUMMARY: The Arctic Ocean will become ice free during summer before mid-century unless greenhouse gas emissions are rapidly reduced.